2011
DOI: 10.1080/09712119.2011.588406
|View full text |Cite
|
Sign up to set email alerts
|

Performance and nutrient digestion of lambs fed incremental levels of wild cactus (Opuntia leucotrichia)

Abstract: In a performance trial, 50 intact Rambouillet )Dorper male lambs (1992.8 kg), were randomly assigned to experimental diets containing 0, 10, 20, 30 or 40%, Opuntia leucotrichia (O. leucotrichia; dry matter basis). At day 91 animals were slaughtered for carcass and meat quality evaluation. In trial two, five ruminal cannulated Rambouillet male rams were used in a digestion study. Dry matter intake, average daily gain and feed efficiency of lambs decreased (P B0.05) generally with increasing levels of O. leucotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The increasing PPPs resulted in more fermentation in the caecal, thus reduced caecal PH as a result of increasing volatile fatty acids production. These results are in agreement with those reported by Bisop, et al (2007), Mendez. Liorente, et al (2008 in sheep, Vieira, et al (2008) in goats and Zeedan, et al (2015) found that cecal PH value and NH3-N concentration were higher (P<0.05) in the control group than those fed with 30,20 and 10% Cactus Opuntia cladodes (COC).…”
Section: Cecum Traits:-supporting
confidence: 94%
“…The increasing PPPs resulted in more fermentation in the caecal, thus reduced caecal PH as a result of increasing volatile fatty acids production. These results are in agreement with those reported by Bisop, et al (2007), Mendez. Liorente, et al (2008 in sheep, Vieira, et al (2008) in goats and Zeedan, et al (2015) found that cecal PH value and NH3-N concentration were higher (P<0.05) in the control group than those fed with 30,20 and 10% Cactus Opuntia cladodes (COC).…”
Section: Cecum Traits:-supporting
confidence: 94%
“…Likewise PPP has been characterized as good source of dietary fiber that enhancing the intestinal health. These results are in agreement with those reported by Zeedan, et al (2015) with rabbits, Mendez-Llorente, et al (2008) with sheep and Vieira et al (2008) with goats. On the other hand, Misra, et al (2006) found that ruminal NH3-N concentration was not significantly different between lambs fed 0, 10 and 20% prickly pear cactus, but were higher than that of the levels of 30 and 40%.…”
Section: Cecum Traitssupporting
confidence: 94%
“…Other scientists (VIEIRA et al, 2008;MENDEZ-LLORATE et al, 2011;COSTA et al, 2012) have reported that increasing the proportion of forage cactus in the diet (above 50%) reduced dry matter intake. Forage cactus has a low dry matter content, which explains the reduction in the DMI; distension of the digestive tract limits the intake of food, even if the nutritional requirements are not met ( VAN SOEST, 1994).…”
Section: Resultsmentioning
confidence: 99%